Optimalisasi Perawatan Orang dengan Gangguan Jiwa (ODGJ) Berbasis Komunitas - Adita Lintang Kharisma Putri; Sri Lestari; Setia Asyanti; Sepi Indriati; Mir'atun Hasanah (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
Treatment of people with mental disorders (ODGJ) is one of the problems in Village C in realizing the Mental Health Alert Village. Lack of family understanding about the care of ODGJ makes the family tend to have a negative attitude towards ODGJ. This activity aims to obtain an overview of the efforts to cure ODGJ, and the obstacles experienced, as well as to design and implement an intervention program to increase the knowledge and skills of families in caring for ODGJ. This activity aims to obtain an overview of the efforts to cure ODGJ, and the obstacles experienced, as well as to design and implement an intervention program to increase the knowledge and skills of families in caring for ODGJ. Data collection techniques used are observation, interviews, and focus group interview. The intervention methods used are advocacy and psychoeducation. The data obtained were analyzed by the Wilcoxon test. From psychoeducation activities, it is known that there is an increase in the participants’s knowledge, understanding, and skills. as indicated by the change in the scale score from 37.25 to 39.25. The family shows behavioral changes in providing care and treatment for ODGJ. Through advocacy activities, it is possible to create a Mental Health Post which will provide services every month to ODGJ families. ABSTRAK Perawatan orang dengan gangguan jiwa (ODGJ) menjadi salah satu permasalahan Desa C dalam mewujudkan Desa Siaga Sehat Jiwa. Pemahaman keluarga yang minim mengenai perawatan ODGJ membuat keluarga cenderung bersikap negatif terhadap ODGJ. Kegiatan ini bertujuan untuk memperoleh gambaran mengenai upaya meyembuhkan ODGJ, dan hambatan yang dialami, serta merancang dan melaksanakan program intervensi untuk meningkatkan pengetahuan dan keterampilan keluarga dalam merawat ODGJ. Kegiatan ini melibatkan 18 orang yang terdiri dari keluarga yang merawat ODGJ, serta masyarakat dan pemerintah desa. Teknik pengumpulan data yang digunakan yaitu observasi, wawancara dan FGI. Metode intervensi yang digunakan yaitu advokasi dan psikoedukasi. Data yang diperoleh dianalisis dengan uji Wilcoxon. Dari kegiatan psikoedukasi diketahui bahwa ada peningkatan pengetahuan, pemahaman, dan keterampilan pada peserta yang ditunjukkan pada perubahan skor skala dari 37,25 menjadi 39,25. Keluarga menunjukkan perubahan perilaku dalam memberikan perawatan dan pengobatan bagi ODGJ. Melalui kegiatan advokasi dapat terwujud Posyandu Jiwa yang akan memberikan layanan setiap bulan pada keluarga ODGJ.